Mechanisms of oxidative stress-induced sperm dysfunction - Wang, Yutao; Fu, Xun; Li, Hongjun (Frontiers in Endocrinology, 2025)
Oxidative stress plays a pivotal role in male infertility by impairing sperm function through various molecular mechanisms. This review explores the impact of excessive reactive oxygen species (ROS) on spermatozoa, particularly focusing on lipid peroxidation, DNA fragmentation, and protein oxidation. Lipid peroxidation damages sperm membranes, reducing fluidity and motility. ROS-induced DNA fragmentation compromises genetic integrity, potentially leading to infertility and adverse offspring outcomes. Protein oxidation alters key structural proteins, impairing sperm motility and the ability to fertilize an egg. The primary sources of oxidative stress in sperm include leukocyte activity, mitochondrial dysfunction, and environmental factors such as smoking and pollution. Despite the presence of natural antioxidant defenses, spermatozoa are particularly vulnerable due to limited repair mechanisms. The review highlights the importance of early intervention through antioxidant therapies and lifestyle changes to mitigate the detrimental effects of oxidative stress on male fertility. Further research is essential to enhance therapeutic approaches and improve reproductive outcomes.